Over Review On Needle Less Injection and Medicated Tattoo Upcoming Trends in Drug Delivery System - Shah, R. R.; Mohite, S. A.; Patel, N. R. (Asian Journal of Pharmaceutical Research and Development, 2017)
Drug delivery system (DDS) plays a vital role and is way to deliver the desired drug to the desired organ sand hence it is attracted by enormous scientist and researchers. This review describes about two novel approaches: 1) needle free injection technology and2) Medicated tattoos. New drug delivery techniques aim to improve overall drug performance and efficacy, making patient’s lives easier. Needle free injection technology is growing and has the potential to make the administration of medicine more efficient, safe and convenient. Needle-free liquid jet injectors have been used for more than 50 years for parenteral delivery of vaccines and drugs. Although excellent bioavailability has been reported for a number of drugs, occasional pain and bruising have limited wide acceptance of jet injectors. Today, they are a steadily developing technology that promises to make the administration of medicine more efficient and less painful. Transdermal drug delivery can improve the therapeutic efficacy and safety of drugs by more site specific way but spatial and temporal placement within body is required to reduce both the size and number of doses necessary to achieve the objective of systemic medication through topical application to the intact skin surface. Medicated Tattoos Med-Tats is a modification of temporary tattoo which contains an active drug substance for transdermal delivery. A comprehensive and thorough literature about medicated tattoo and needless injection is placed in this article